The Role of KPPU in Protecting Retail Business and Traditional Market in Indonesia During The Era of Market Liberalization (Lex Jurnalica, 2008)
Nowadays, The Indonesian government has actively carried out liberalization within economic sector. Started since The 1997 financial crisis and the insistence of the IMF that a number of policy reforms be introduced created a dramatic change in the regulatory environment in Indonesia. The government urged Parliament to pass the Bill of Investment Law, and convinced them that the new law will attract foreign investor to cultivate their capital in Indonesia. The law number 25/2007 at last issued and prevailed for any business players in Indonesia regardless the original of Business Company come from. Nevertheless, many people, in particular, small business players worry about the impact of such rules which is clearing away and impact to their business or jobs. On the contrary, that phenomenon has actually shown a better condition of economic and lifestyle that makes people enjoy hygiene and leisure sphere of mall, supermarket, and department stores that nice and clean. But, anyhow, it evokes anxiousness and distrustful around the business people who think those modern marketplaces will become a threat for traditional market existence.Keywords: Protecting, Retail Business and Traditional Market, In Indonesia